Monk-Led Missions between Ming China and Malla Nepal - Sen, Kuan (Prajñā Journal of Buddhist Studies, 2026)
Buddhism has played an important role as a bridge and link in strengthening the friendship between China and Nepal. During the Ming Dynasty, official exchanges between these two countries were frequent. Based on an analysis of historical literatures, this study systematically organized the official communication records of both sides and identified their characteristics, including the temporal concentration, the predominantly monastic delegates, and the use of the Ancient Bo-Ni Road. The article examines and discusses these peculiarities, their causes and the remaining issues, in order to illustrate the essential role of outstanding monks in the history of Sino-Nepal diplomacy, and to provide a historical reference for modern exchanges in Buddhist culture.